ANALISI PENGARUH RESIKO MANIPULASI EARNINGS DAN RESIKO CORPORATE GOVERNANCE TERHADAP PERENCANAAN AUDIT PADA KANTOR AKUNTAN PUBLIK (KAP) DI PALEMBANG - Sonang PP (JURNAL KOMPETITIF, 2015)
The following research investigates the effects of Earnings Manipulation risk and Corporate Governance Risk on audit planning. Audit planning, followed by well-executed and well-implemented corporate governance, should reduce earnings manipulation risk.Population of this research is auditors who work in Public Accounting Firm in Palembang. Questionnaires are used as main method for collecting data. Multiple regression is used for analysis. The data for this research is obtained from a group of auditors who work in public accounting firm located in Palembang.The result of this research shows that earnings manipulation risk significantly and positively affects audit planning and Corporate Governance risk significantly and positively affects audit planning. In other words, earnings manipulation risk and corporate governance risk mutually affect audit planning in significant and positive manner.Ã‚Â Keywords: earnings manipulation, corporate governance, and audit planning.